2022
DOI: 10.1093/advances/nmab126
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Vitamin D Supplementation on Vitamin D Status of Exclusively Breastfeeding Mothers and Their Nursing Infants: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: The optimal vitamin D supplementation plan during lactation is unclear. We investigated the effect of maternal vitamin D supplementation on mother-infant dyads' vitamin D status during lactation. All controlled trials that compared vitamin D supplements to placebo or low doses of vitamin D in breastfeeding mothers were included. Pooled effect size and the associated 95% confidence interval (CI) for each outcome were estimated using random-effects models. A one-stage random-effect dose-response model was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Similar findings were subsequently reported from a larger randomized controlled trial with maternal doses of 6,400 IU in the USA, whereas the same study found that maternal doses of 2,400 IU did not support infant vitamin D status ( 62 ). A recent meta-analysis of maternal vitamin D supplementation and its effect on milk vitamin D content and infant vitamin D status reported a significant increase in milk ARA with vitamin D supplementation and a prediction equation of “ARA = 0.099 × vitamin D dose (IU/D) -30” ( 71 ). In addition, the authors calculated that for each 1,000 IU of maternal vitamin D supplementation, infant 25(OH)D concentration increased by 6.8 nmol/L ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were subsequently reported from a larger randomized controlled trial with maternal doses of 6,400 IU in the USA, whereas the same study found that maternal doses of 2,400 IU did not support infant vitamin D status ( 62 ). A recent meta-analysis of maternal vitamin D supplementation and its effect on milk vitamin D content and infant vitamin D status reported a significant increase in milk ARA with vitamin D supplementation and a prediction equation of “ARA = 0.099 × vitamin D dose (IU/D) -30” ( 71 ). In addition, the authors calculated that for each 1,000 IU of maternal vitamin D supplementation, infant 25(OH)D concentration increased by 6.8 nmol/L ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of maternal vitamin D supplementation and its effect on milk vitamin D content and infant vitamin D status reported a significant increase in milk ARA with vitamin D supplementation and a prediction equation of “ARA = 0.099 × vitamin D dose (IU/D) -30” ( 71 ). In addition, the authors calculated that for each 1,000 IU of maternal vitamin D supplementation, infant 25(OH)D concentration increased by 6.8 nmol/L ( 71 ). These data suggest that lower doses of maternal vitamin D supplementation are unlikely to provide a milk vitamin D content sufficient to meet a vitamin D intake of 400 IU/d ( 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggested that highdose maternal vitamin D supplementation during lactation with 4000-6400 IU daily of vitamin D substantially increases mother and infant vitamin D status without adverse events (24). A recent metaanalysis study implied that long-term maternal supplementation with vitamin D at a high dose (> 6000 IU/day) effectively corrected vitamin de ciency in both mothers and infants (25,26). Therefore, only maternal vitamin D supplementation with high-dose could supplies breast milk with adequate vitamin D to satisfy her nursing infant's needs and offers a strategy to direct infant vitamin D de ciency.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers aged 23-30 years old had signi cantly lower 25(OH)D level compared with these aged 31-42 years (15.32 ± 0.87 ng/mL vs. 20.40 ± 1.74 ng/mL, p = 0.02) during lactation. Women who had delivered a previous child had higher25(OH)D level in comparison to women without a history of delivery (20.52 ± 14.45 ng/mL vs. 16.76 ± 7.91 ng/mL, p = 0.04). The serum 25(OH)D concentration was highest in postpartum mothers who had more than 400 IU/daily vitamin D intake in pregnancy and those who had none or less than 400 IU/daily intake(p = 0.04) (Table1).…”
mentioning
confidence: 93%
“…A 2021 meta-analysis of 19 trials, (n = 3337 breastfeeding mothers), evaluated the effect of maternal vitamin D supplementation on the circulating 25(OH)D levels of the lactating mother and infant and found that vitamin D supplementation in the lactating mother is associated with a nonlinear increase in 25(OH)D levels in the lactating mother, and a linear relationship with infants' serum 25 (OH)D levels. 109 A maternal dose of >150 mcg of vitamin D3 was sufficient to substitute for 10 mcg of vitamin D for the infant. However, they cautioned that more research is needed to confirm this as a policy change.…”
Section: Vitamin D and Chronic Painmentioning
confidence: 99%